2019
DOI: 10.2105/ajph.2018.304768
|View full text |Cite
|
Sign up to set email alerts
|

California’s Senate Bill 277: Local Health Jurisdictions’ Experiences With the Elimination of Nonmedical Vaccine Exemptions

Abstract: Objectives. To understand the experiences of local health jurisdictions with Senate Bill 277 (SB277), the California law that eliminated nonmedical vaccine exemptions for public- and private-school entry. Methods. We conducted semistructured telephone interviews with health officers and local health department (LHD) staff in California between August and September 2017. Results. Two overall themes emerged: (1) vague legislative and regulatory language led to variation in the interpretation and implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In California, lack of clear guidance on qualifying medical conditions, authority to grant medical exemptions, and which institutions, if any, bear responsibility for monitoring medical exemptions has likely contributed to the uneven increases in these exemptions across the state. 36,37 It is essential that those with the authority to grant or review exemptions be aware of the danger that spatial clustering of vaccine refusals presents for both infections in local communities and sustained transmission in the population. 38 Our results confirmed that spatial clustering of exemptions lead to underestimations of outbreak potential.…”
Section: Discussionmentioning
confidence: 99%
“…In California, lack of clear guidance on qualifying medical conditions, authority to grant medical exemptions, and which institutions, if any, bear responsibility for monitoring medical exemptions has likely contributed to the uneven increases in these exemptions across the state. 36,37 It is essential that those with the authority to grant or review exemptions be aware of the danger that spatial clustering of vaccine refusals presents for both infections in local communities and sustained transmission in the population. 38 Our results confirmed that spatial clustering of exemptions lead to underestimations of outbreak potential.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we found evidence to suggest that the law was variably interpreted, implemented, and enforced across school districts given vague regulatory language. 11,29 One study found that the number of students "overdue" for vaccination more than quadrupled 3 , suggesting that some parents were being allowed to enroll their children in brick-and-mortar schools despite being under-or unvaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Following the implementation of SB 277, data from the California Department of Public Health 9,10 showed that the law proved effective in increasing vaccine uptake with Kindergarten immunization rates increasing from 92.8% in 2015-16 to 95.1% in 2017-18. 11 There was a concern, however, that the law created an incentive for parents who could no longer obtain a nonmedical exemption to either substitute a medical exemption 12 or to homeschool their children in order to circumvent school entry immunization requirements (a new provision of SB277). 13 In fact, the medical exemption rate for Kindergarteners almost tripled between 2015-2016 and 2017-2018 11,14 ; when many of these were suspected of being fraudulent, the legislature passed Senate Bill No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the implementation of SB 277, data from the California Department of Public Health 9,10 showed that the law proved effective in increasing vaccine uptake, with kindergarten immunization rates increasing from 92.8% in the 2015-2016 school year to 95.1% in the 2017-2018 school year. 11 However, investigators were concerned that the law created an incentive for parents who could no longer obtain a nonmedical exemption to either substitute a medical exemption 12 or to homeschool their children and thereby circumvent school entry immunization requirements (a new provision of SB 277). 13 In fact, the medical exemption rate for kindergarteners almost tripled from the 2015-2016 to 2017-2018 school years 11,14 ; when many of these exemptions were suspected of being fraudulent, the legislature passed Senate Bill No.…”
Section: Introductionmentioning
confidence: 99%